Base-Mediated Addition of 1-(2-Hydroxyalkyl)pyrroles to Acetylene: Atom-Economic Route to 1-[2-(Vinyloxy)alkyl]pyrroles - Sadykov, Evgeny Kh.; Lobanova, Natalya A.; Stankevich, Valery K. (Synthesis, 2015)
Nucleophilic addition of 1-(2-hydroxyalkyl)pyrroles to acetylene, an unactivated carbon–carbon triple bond, in the presence of a base has been studied. As a result an atom-economic synthetic method to obtain 1-[2-(vinyloxy)alkyl]pyrroles in good yields employing superbase, sodium or potassium hydroxide in dimethyl sulfoxide, systems has been developed. 1-[2-(Vinyloxy)alkyl]pyrroles are cleaved by base with the elimination of vinyl alcohol to give 1-vinylpyrroles.
Keywords: acetylene; addition; alcohol; pyrrole; vinyl ether